2021
DOI: 10.3390/toxics9050098
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Protein Adduction in Toxic Neuropathies of Exogenous and Endogenous Origin

Abstract: The peripheral (axonal) neuropathy associated with repeated exposure to aliphatic and aromatic solvents that form protein-reactive γ-diketones shares some clinical and neuropathological features with certain metabolic neuropathies, including type-II diabetic neuropathy and uremic neuropathy, and with the largely sub-clinical nerve damage associated with old age. These conditions may be linked by metabolites that adduct and cross-link neuroproteins required for the maintenance of axonal transport and nerve fibe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 148 publications
(175 reference statements)
0
6
0
Order By: Relevance
“…32 Although 2,5-HD is the ultimate neurotoxic metabolite of n-hexane, it is detectable (mean urinary 2,5-HD: 0.35-1.47 mg/L, median pyrrole adducts: 0.91-7.4 μM) in populations with no known occupational or environmental exposure to n-hexane or 2-hexanol. 10 The origin of endogenous 2,5-HD is unclear, but it may result from lipid oxidation, which also generates γ-ketoaldehydes. The commonly used method to detect urinary 2,5-HD measures both free 2,5-HD and 4,5-dihydroxy- 2-hexanone, 33 a reduction product of 3-HHD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…32 Although 2,5-HD is the ultimate neurotoxic metabolite of n-hexane, it is detectable (mean urinary 2,5-HD: 0.35-1.47 mg/L, median pyrrole adducts: 0.91-7.4 μM) in populations with no known occupational or environmental exposure to n-hexane or 2-hexanol. 10 The origin of endogenous 2,5-HD is unclear, but it may result from lipid oxidation, which also generates γ-ketoaldehydes. The commonly used method to detect urinary 2,5-HD measures both free 2,5-HD and 4,5-dihydroxy- 2-hexanone, 33 a reduction product of 3-HHD.…”
Section: Discussionmentioning
confidence: 99%
“… 8 Because aliphatic and aromatic γ‐diketones are established causes of distal symmetrical axonal neuropathy in humans and laboratory animals, 9 pyrrole‐protein reactions may be relevant to axonal neuropathies in diabetic states. 10 Here, we test the hypothesis that both plasma pyrrole adducts (PP) and adjusted urinary pyrrole adducts (aUP) are associated with glucose indices, that is, fasting blood glucose (FBG) and glycate hemoglobin A1c (HbA1c), and these associations are linked with some clinical features of DSPN. Our data are consistent with the hypothesis and set the stage for further clinical studies to examine the relationship between diabetic diffuse neuropathies and protein pyrrole adducts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that this metabolic route involves a non-enzymatic aldol-reaction between MG and the ketone body acetoacetate, leading to 3-hydroxyhexane-2,5-dione, which is present in the blood of insulin-starved patients. Alternative pathways that might compensate the deficiency of glyoxalase system could potentially generate toxic molecules such as γ-diketones, which are associated with peripheral axonal degeneration and testicular injury [97,98].…”
Section: Alternative Detoxification Mechanisms As Putative Backup Systems To Compensate the Lack Of Glyoxalase Activitymentioning
confidence: 99%
“…Proteins can covalently adduct with xenobiotic compounds from exposure to endogenous or exogenous chemicals, such as drugs, pesticides, or their metabolites, at active amino acid residues [ 1 8 ]. Research over the past half century has demonstrated that these protein adducts might lead to multiple health issues, including cancer and immune system effects [ 1 , 5 , 7 , 9 13 ]. Therefore, identification of xenobiotics adducted to key proteins and identification of the sites of adduction within the protein are important to better understand the events underlying diseases and chemically induced adverse reactions.…”
Section: Introductionmentioning
confidence: 99%